Factors attributable for the prevalence of dental caries in Queensland children. Issue 5 (21st April 2015) - Do, Loc Giang; Ha, Diep Hong; Spencer, A. John
Abstract Background Dental caries is a multifactorial condition, prevention of which requires comprehensive understanding of both contextual and compositional determinants and their population impact. Aims To investigate contextual and compositional factors associated with the prevalence of dental caries in children and to estimate the population impact of those factors. Methods Children in one Australian state were selected through stratified random sampling selection in 2010–2011. Oral epidemiological examinations provided individual‐level outcomes: prevalence of dental caries in the primary (among 5‐ to 8‐year‐olds) and permanent dentitions (9‐ to 14‐year‐olds). Socioeconomic status, oral health behaviours and practices and dietary patterns were explanatory factors at the individual‐level, school‐level and area‐level fluoridation status. Three‐level multilevel multivariable models were sequentially specified for the prevalence of dental caries to estimate prevalence ratios (PR) associated with explanatory factors, adjusting for covariates and between‐ and within‐group variances. Population attributable fraction (PAF) was estimated as the population impact of the statistically significant explanatory factors. Results Data from 2214 5‐ to 8‐year‐olds and 3186 9‐ to 14‐year‐olds from 207 schools in 16 areas were analysed. The prevalence of dental caries in the primary and the permanent dentitions was 47.1% (43.9–50.4) and 38.8% (36.1–41.6), respectively. The highest prevalence of dental caries was observed in the nonfluoridated areas. In bivariate associations, factors at three levels were associated with prevalence of dental caries. In the full models, children in the nonfluoridated areas had significantly higher prevalence of dental caries [PR for the primary: 1.29 (1.11–1.50); PR for the permanent 1.49 (1.01–2.21)] compared with children in fluoridated areas, controlling for other factors. PAF estimates indicated that lack of water fluoridation attributed to 21% and 31% of primary and permanent dental caries, respectively in this child population. Conclusion A multitude of factors had significant population impact on the prevalence of dental caries in children. Water fluoridation has a significant population impact on dental caries experience in this child population.